Stability of bromelain-polyphenol complex in pineapple juice - Abdul Majid, Fadzilah Adibah (Penerbit UTM Press, 2008)
Pineapple posseses many beneficial properties for the human health due to high content of bromelain. The most natural ways to consume bromelain is by eating fresh fruit or by drinking fresh pineapple juice. However, processed pineapple juice is relatively easy and convenient to buy, transport and stored for later use. Canned or packed juices are usually processed under high temperature. This heat treatment for sterilisation purposes may contribute to enzyme and other heat sensitive components in the juice be denatured, especially bromelain. Polyphenol compounds was previously reported to stabilize bromelain. In this work, we reported the stability of bromelain in pineapple juice complexed with polyphenol compounds from fresh apple juice. The mixed pineapple-apple juice was prepared under various heating temperatures and sterilization holding times. The bromelain concentration and activity in prepared juices were determined using HPLC using spesific column. Our study shows that the bromelain-polyphenol complex enhanced bromelain thermal stability and the shelf life of juice when stored at lower temperature.